Effect of acute submaximal physical exercise before decompression dive on tumor necrosis factor alpha concentration among male trained divers - Chikih Chikih; Guritno Suryokusumo; Astrid Sulistomo (International Journal of Public Health Science (IJPHS), 2021)
The increase of inflammatory biomarkers due to decompression dive is one of the factors that could cause decompression sickness (DCS), one of them is tumor necrosis alpha (TNFα). According to the preconditioning theory, exercise before dive can reduce amount of gas bubble to prevent DCS. This study aimed to prove that exercise before diving can prevent increase of TNFα. This study employed quasi-experimental design with trained male divers. The subject divided into two groups, treatment and control. The treatment group got submaximal exercise with 70% heart rate intensity, using cycle ergometer with young men's Christian association (YMCA) procedure modify by Guritno, 24 hours before decompression dive 280 kPa bottom time 80 minute with US-NAVY table, whereas the control group only do decompression dive. TNFα expression was checked three times, at beginning of study, before dive and after dive. In treatment group there was insignificant decrease TNFα, from 7.06±1.85pg./ml to 6.75±1.81pg./ml, whereas the control group showed a significant increased TNFα, from 8.22 (1.45 to 13.11)pg./ml to 8.39 (1.73 to 12.18)pg/ml, and significant difference was found between the mean difference for two groups p<0.05. It can be concluded that acute submaximal exercise prevents an increase of TNFα after single dive decompression to prevent possibility occurring DCS).